Phenotypes and Genotypes of Patients with Pantothenate Kinase-Associated Neurodegeneration in Asian and Caucasian Populations: 2 Cases and Literature Review. (19th November 2013) - Lee, Chih-Hong; Lu, Chin-Song; Chuang, Wen-Li; Yeh, Tu-Hsueh; Jung, Shih-Ming; Huang, Chia-Ling; Lai, Szu-Chia
Abstract : Objectives . Pantothenate kinase-associated neurodegeneration (PKAN) is a rare disease caused by pantothenate kinase 2 ( PANK2, OMIM 606157) mutations. This study is aimed to investigate clinical presentations, pathologies, and genetics in patients with PKAN. Methods . Two patients with PKAN were reported. We reviewed the literature to include additional 19 patients with PKAN in Eastern Asia. These patients were divided into classic and atypical groups by the age of onset. We compared the data on PKAN patients of Asian and Caucasian populations. Results . We found iron deposits in the globus pallidus in our Patient 1 and a heterozygous truncating mutation (c.1408insT) in Patient 2. Literature review shows that generalized dystonia and bulbar signs are more common in classic PKAN patients, whereas segmental dystonia and tremors are more specific to atypical ones. Asian patients have less complex presentations—lower prevalence of pyramidal signs, mental impairment, and parkinsonism—than Caucasians. D378G in exon 3 is the most frequent mutation (28%) in Asians. Conclusions . Our study demonstrates that the distribution of dystonia is the major distinction between subgroups of PKAN. Caucasian patients have more complex presentations than Asians. Exon 3 and 4 are hot spots for screening PANK2 mutations in Asian patients.